Pendekatan Realistic Mathematics Education Pada Materi Bentuk Aljabar - Moh Syukron Maftuh; Via Yustitia (Jurnal Inovasi Matematika, 2021)
Realistic Mathematics Education (RME) is a learning approach that links mathematics with real-world contexts, making it easier for students to solve mathematical problems. This study aimed to describe student activities, learning outcomes, and student responses by implementing RME in junior high school students. The method used was descriptive quantitative. This research was conducted in class VII SMPN 1 Wonoayu, Sidoarjo. The method used was the method of observation, tests, and questionnaires. Instruments in the form of student activity observation sheets, learning outcomes tests, and response questionnaires. The observations showed that the student activity was in a suitable category, reaching 79.46%. The percentage of classical completeness of learning outcomes through the implementation of RME was 84.37%, so it was classically good. Student responses obtained positive results with a percentage of 91.01% classically, so it was categorized as very positive.